PECULIARITIES OF MICROSOMAL FUNCTION OF LIVER UNDER CONDITIONS OF CHRONIC EPILEPTIC ACTIVITY INDUCTION AND EXPERIMENTAL TREATMENT - Polyasny, V.A. (World of Medicine and Biology, 2012)
Under conditions of chronic experiment on Wistar rats with corazol- induced (25,0 mg/kg, i.p.) kindling the pronounced disturbances of the activity of cytochrom P450 were registered. Besides, the ratio of Р450/Р420 was decreased, and the activity of cytochrom b5.was decreased. The disturbances in the phospholipids turnover were observed as well and these manifestations were more pronounced in postponed kindling and subthreshold corazol administration. Ketogenic diet and pentoxyphyllin (50,0 mg/kg, i.p.) administration normalized the general content of microsomal phospholipids, and the enhanced the level of lyzophosphat-idilcholine. The preservation of functional activity of cytochrom P450 as well as significant increasing of amidopirin-N- demethylase and anylin-n- hydroxylase activities were observed as well. Besides, the increasing of cytochrom b5.was registered.
Keywords: kindling; ketogenic diet; pentoxyphyllin; pospholipids; liver